Patients and professionals have different views on online patient information about cleft lip and palate (CL/P). Issue 6 (June 2016) - van den Bosch, S.; Koudstaal, M.; Versnel, S.; Maal, T.; Xi, T.; Nelen, W.; Bergé, S.; Faber, M.
Abstract: Parents of children with a cleft lip and/or palate (CL/P) and patients with CL/P actively search for online information about CL/P. The quality of this information has not been sufficiently evaluated. The aim of this study was to define quality criteria for online information about CL/P and assess the quality of frequently accessed websites. Patients, parents, and professionals were equally involved in all stages of this study. A literature review was performed to obtain known quality criteria for online information. These criteria were prioritized by patients, parents, and professionals. The most important criteria were used to rate the quality of four websites on CL/P. Forty-two quality items were extracted from the literature. Patients, parents, and professionals agreed on the importance of 16 of these items. New groups of patients, parents, and professionals assessed four websites on CL/P. Although the groups were like-minded in their overall assessment of the quality of the websites, distinct differences emerged between the groups in relation to certain items. This study shows the importance of patient participation in healthcare research, as well as a feasible approach to do so. Involving patients in composing online health information will set different priorities, which is necessary in establishing high quality information.